2017
DOI: 10.1002/aur.1742
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Autistic Traits in Children Aged 2 to 4½ Years With the Preschool Version of the Social Responsiveness Scale (SRS‐P): Findings from Japan

Abstract: The recent development and use of autism measures for the general population has led to a growing body of evidence which suggests that autistic traits are distributed along a continuum. However, as most existing autism measures were designed for use in children older than age 4, to date, little is known about the autistic continuum in children younger than age 4. As autistic symptoms are evident in the first few years, to address this research gap, the current study tested the preschool version of the Social R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 62 publications
(85 reference statements)
4
16
0
Order By: Relevance
“…In a study with a community sample of school-aged children (ages 7 to 9) [ 34 ], the Cronbach’s alpha coefficient was 0.86: A similar level of internal consistency for the ASSQ for preschool children was also found. The internal consistency of the ASD screening instrument, which is similar to the ASSQ applied to preschool children, was 0.99 for the Autism Spectrum Quotient: Children’s Version (AQ-Child) [ 23 ]; 0.891–0.942 for the preschool version of the Social Responsiveness Scale (SRS-P) [ 50 ]; and 0.839 for the Childhood Autism Spectrum Test (CAST) [ 51 ]. As a coefficient, internal consistency tends to increase as the number of items on a scale increases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study with a community sample of school-aged children (ages 7 to 9) [ 34 ], the Cronbach’s alpha coefficient was 0.86: A similar level of internal consistency for the ASSQ for preschool children was also found. The internal consistency of the ASD screening instrument, which is similar to the ASSQ applied to preschool children, was 0.99 for the Autism Spectrum Quotient: Children’s Version (AQ-Child) [ 23 ]; 0.891–0.942 for the preschool version of the Social Responsiveness Scale (SRS-P) [ 50 ]; and 0.839 for the Childhood Autism Spectrum Test (CAST) [ 51 ]. As a coefficient, internal consistency tends to increase as the number of items on a scale increases.…”
Section: Discussionmentioning
confidence: 99%
“…As such, a scale needs to be compared with another scale with a similar number of items. Of the three scales mentioned above, the AQ-Child had 50 items [ 23 ], the SRS-P had 65, [ 50 ] and the CAST had 37 [ 51 ]. Even with regard to the number of items, the ASSQ’s internal consistency is believed to be satisfactory to a certain level as a screening instrument for the same age group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SRS is a 65-item survey-based instrument that quantitatively assesses the presence and severity of autistic traits in children and adults in the general human population [Chan, Smith, Hong, Greenberg, & Mailick, 2017;Constantino & Gruber, 2012]. The SRS was developed for use in the United States, but has since been shown to accurately measure autistic traits in multiple and diverse human societies [Bölte, Poustka, & Constantino, 2008;Jussila et al, 2015;Stickley et al, 2017]. Importantly, SRS scores of ASD-diagnosed vs. unaffected siblings differ robustly at 1.5 standard deviations above the general population mean [Constantino, 2011;Constantino, Zhang, Frazier, Abbacchi, & Law, 2010;Virkud, Todd, Abbacchi, Zhang, & Constantino, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…However, investigations of general mental and neurocognitive development have not been fully standardized. The results of a recent systematic study have suggested that the preschool version of the Social Responsiveness Scale identifies the distribution of autistic symptoms as a continuum in children younger than age 4 (Stickley et al, ). These questionnaires, which are obtained by mothers, fathers, or other caregivers, could be very useful for investigating ASD in toddlers.…”
Section: Introductionmentioning
confidence: 99%